Rancangan Penentuan Lokasi Crushing Plant Sirtu CV Brilliant Ningrat di Kecamatan Leles, Kabupaten Garut, Provinsi Jawa Barat - Zharfan Ghana; Yunus Ashari; Noor Fauzi Isniarno (Bandung Conference Series: Mining Engineering, 2023)
Abstract. CV Brilliant Ningrat is a company engaged in rock mining with sirtu commodities in Leles District, Garut Regency, West Java Province. In determining the location of the Crushing Plant, supporting data is needed which will strengthen the arguments in determining the location of the Crushing Plant. In this study the supporting data is the soil bearing capacity of the Terzaghi method. The soil bearing capacity of the Terzaghi method plays a role in calculating the foundation to be stepped on by the Crushing Plant. To obtain supporting data using the soil bearing capacity of the Terzaghi method, data are needed in the form of soil density (ρ), soil cohesion (C) and soil inward shear angle (ϕ). The results of testing the soil samples, obtained the largest soil density (ρ) value of 1.67 gr/cm3, the largest soil cohesion (C) value of 0.016 and the largest soil shear angle (ϕ) value of 15.86o. This value will be included in the soil bearing capacity of the Terzaghi method and will produce a value of 8.74 KPa. Referring to SNI 8460:2017, the bearing capacity of the foundation permit from the bearing capacity of the soil is divided by a minimum safety factor of 3 for shallow foundations. So that the value of the permit bearing capacity is 2.91 KPa. The Crushing Plant land preparation stage uses the Cut and Fill method. Based on the results of calculating the stripping volume of the Crushing Plant obtained from the Crushing Plant Topographic Map using AutoCAD software, it shows that the area to be stripped is 85875.51 LCM consisting of top soil material of 28387.81 LCM and sirtu material of 57487.70 LCM. Abstrak. CV Brilliant Ningrat adalah perusahaan yang bergerak dibidang penambangan batuan dengan komoditi sirtu di Kecamatan Leles, Kabupaten Garut, Provinsi Jawa Barat. Pada penentuan lokasi Crushing Plant dibutuhkan data pendukung yang akan memperkuat argumentasi dalam penentuan lokasi Crushing Plant. Pada penelitian ini data yang menjadi pendukung berupa daya dukung tanah metode Terzaghi. Daya dukung tanah metode Terzaghi ini berperan untuk membuat perhitungan pondasi yang akan dipijak oleh Crushing Plant. Untuk mendapatkan data pendukung yang menggunakan daya dukung tanah metode Terzaghi diperlukan data berupa density tanah (ρ), kohesi tanah (C) dan sudut geser dalam tanah (ϕ). Hasil dari pengujian sampel tanah, didapatkan nilai density tanah (ρ) terbesar senilai 1,67 gr/cm3, kohesi tanah (C) terbesar senilai 0,016 dan sudut geser dalam tanah (ϕ) terbesar senilai 15,86o. Nilai ini akan dimasukkan kedalam daya dukung tanah metode Terzaghi dan menghasilkan nilai sebesar 8,74 KPa. Mengacu kepada SNI 8460:2017, daya dukung izin pondasi dari daya dukung tanah dibagi dengan faktor keamanan besarnya minimum 3 untuk pondasi dangkal. Sehingga nilai dari daya dukung izin sebesar 2,91 KPa. Tahap penyiapan lahan Crushing Plant menggunakan metode Cut and Fill. Berdasarkan hasil perhitungan volume pengupasan Crushing Plant yang didapatkan dari Peta Topografi Crushing Plant menggunakan perangkat lunak AutoCAD, menunjukkan area yang akan dikupas sebesar 85875,51 LCM terdiri dari material top soil sebesar 28387,81 LCM dan material sirtu sebesar 57487,70 LCM.